Synthesis and characterization of nanostructured ternary MAX-phase thin films prepared by magnetron sputtering as precursors for twodimensional MXenes - Miranda Marti, Marta (2023)
MAX phase thin films can be fabricated through firstly depositing a precursor thin film consisting of the initial elements M, A, and X close to the MAX phase stoichiometry employing physical vapor deposition techniques with a subsequent thermal annealing process. This work presents different deposition configurations (multilayer and co-sputtering) for the fabrication of the Ti2AlC and Ti3AlC2 MAX phase thin films by magnetron sputtering from three elemental targets (Ti, Al, and C). It was found that the depositions followed mainly amorphous thus the MAX phase was not able to form. By implementing the deposition parameters such as temperature and substrate voltage, the deposition morphology could be tailored to crystalline and MAX phases could be created. Moreover, Ti2AlC and Ti3AlC2 nanostructured MAX phase thin films were fabricated by magnetron sputtering with three elemental targets (Ti, Al, and C) at oblique angle, resulting in a columnar thin film, and the properties of the thin film were described as a function of the column tilt angle. Lastly, the MAX phases at normal configuration and at oblique angle configuration were wet etched and the properties of the resulting MXene thin films were analyzed. It was demonstrated that only the surface of the sample was attacked by the etching solution. Thus, only the surface of the MAX phase was transformed into MXene. This hypothesis was verified by multiple characterizations such as e.g., X-Ray Diffraction and Raman spectroscopy to understand the possible morphology and chemical transformation and its influence on the etched thin film properties. The aim of this work is to unravel the connection between the morphology of the MAX phase thin films and the properties of the resulting MXenes. By understanding this relationship, it would be possible to tailor their features for specific applications.